Spices for Sustainable Development in Northeast Region - Dinesh, R; Thomas, Lijo; Srinivasan, V (Indian Horticulture, 2024)
The spice crops, which form a unique segment within the agricultural sector due to its high income generation potential and export orientation, is an important part of the agrarian economy of the Northeast Region (NER). A wide variety of spice crops, both indigenous and exotic, are cultivated in diverse agro-climatic conditions across the eight states of the NER. Spices play an important role in the economy and culture of the region. They are a major source of income for farmers and provide employment to a large number of people in the region. Spices are also an essential part of the Northeastern cuisine, adding their unique flavour and aroma to dishes.